Actualización del plan de mantenimiento preventivo del banco de motor diésel de la Universidad Antonio Nariño - Sede Farallones - Vidal Montoya, Juan David (Universidad Antonio Nariño, 2022)
This document presents a work plan in which the preventive maintenance to the test bench of diesel engine of the Antonio University Nariño, Farallones Headquarters. this maintenance was carried out in order to correct and avoid potential consequences of your prolonged detention as a result of the restrictions imposed by the pandemic Covid 19 virus. The purpose of the work is based on reviewing, repairing and reactivating the bank, giving students the opportunity to use the diesel engine bank as a resource pedagogical for tests and studies of the same. With the experience of what happened, also proposes to propose a plan of storage for future contingencies and avoid the initial problem